Output analysis and capacity configuration of green backup power supply in data center. Issue 1 (1st October 2022) - Li, Xudong; Song, Jieying; Yang, Peng; Dong, Zengbo; Yang, Shihui; He, Jinwei
Abstract: The backup power supply ensures the stability and reliability of the power supply for a data center. Starting from green backup power supply, this paper studies the selection and configuration method of energy storage mode of backup power supply according to the backup power demand of data center and peak regulation demand of power grid, and analyzes different forms of green backup power supply and the output characteristics of hydrogen fuel cell. Aiming at improving the economy of green backup power assisted peak regulation, the capacity configuration principles of hydrogen energy storage and electrochemical energy storage technology are clarified, and then the capacity configuration of standby power in data center is simulated. The results show that the capacity configuration requirements of lithium battery, fuel cell and hydrogen storage tank corresponding to engineering life can be obtained through algorithm optimization.